Identifying potential sources of iron-binding ligands in coastal Antarctic environments and the wider Southern Ocean - Smith, Abigail J.R.; Nelson, Talitha; Ratnarajah, Lavenia; Genovese, Cristina; Westwood, Karen; Holmes, Thomas M.; Corkill, Matthew; Townsend, Ashley T.; Bell, Elanor; Wuttig, Kathrin; Lannuzel, Delphine (Frontiers in Marine Science, 2022)
The availability of iron (Fe) to marine microbial communities is enhanced through complexation by ligands. In Fe limited environments, measuring the distribution and identifying the likely sources of ligands is therefore central to understanding the drivers of marine productivity. Antarctic coastal marine environments support highly productive ecosystems and are influenced by numerous sources of ligands, the magnitude of which varies both spatially and seasonally. Using competitive ligand exchange adsorptive cathodic stripping voltammetry (CLE-AdCSV) with 2-(2-thiazolylazo)-p-cresol (TAC) as a competing artificial ligand, this study investigates Fe-binding ligands (FeL) across the continental shelf break in the Mertz Glacier Region, East Antarctica (64 - 67°S; 138 - 154°E) during austral summer of 2019. The average FeL concentration was 0.86 ± 0.5 nM Eq Fe, with strong conditional stability constants (Log KFeL) averaging 23.1 ± 1.0. The strongest binding ligands were observed in modified circumpolar deep water (CDW), thought to be linked to bacterial Fe remineralisation and potential siderophore release. High proportions of excess unbound ligands (L') were observed in surface waters, as a result of phytoplankton Fe uptake in the mixed layer and euphotic zone. However, FeL and L’ concentrations were greater at depth, suggesting ligands were supplied with dissolved Fe from upwelled CDW and particle remineralisation in benthic nepheloid layers over the shelf. Recent sea-ice melt appeared to support bacterial production in areas where Fe and ligands were exhausted. This study is included within our newly compiled Southern Ocean Ligand (SOLt) Collection, a database of publicly available Fe-binding ligand surveys performed south of 50°S. A review of the SOLt Collection brings attention to the paucity of ligand data collected along the East Antarctic coast and the difficulties in pinpointing sources of Fe and ligands in coastal environments. Elucidating poorly understood ligand sources is essential to predicting future Fe availability for microbial populations under rapid environmental change.